Analysis of the Work Process of Archival Entry Letters at the Administrative Section of the General Bureau of the Regional Secretariat of North Sumatra Province - Silvi Tri Wardani; Nur Ahmadi Bi Rahmani (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2022)
Letters are written communication media used by the sender in order to provide information and news to the recipient. Letters also have an archiving function that contains records of activities from related agencies. The author's signature contained in the letter is a strong sign of the validity of the order and can also be used as evidence or as a basis for taking certain actions. Letters which are also included in the matter of archives. Management and filing of letters is a process that includes the creation, recording, and archiving of all categories, both incoming and outgoing letters in an agency. Incoming letters are categorized as follows: Individual letters for leaders, secretaries, employees, and other official letters that require follow-up. Categorize official letters into routine service letters, important official letters, and secret service letters. The objectives of this study include: 1) Knowing the management of incoming mail archives in the Administrative Section (TU) of the General Bureau of the Regional Secretariat (SEKDA) of North Sumatra Province (SUMUT); 2) Knowing the inhibiting factors in the management of incoming mail archives; 3) Knowing the solution or handling of obstacles in the management of incoming mail archives. The research design is descriptive qualitative. The research was conducted at the TU Section of the General Bureau of the SEKDA of the Province of North Sumatra.